Cultural-Based Contextual Learning Design Material Area and Circumference of the Square Through Tools Ancak - M. Gunawan Supiarmo; Sri Harmonika; Muhammad Wiranadi Utama; Tarmuzi Tarmuzi (JURNAL PENDIDIKAN MATEMATIKA, 2022)
The 2013 curriculum in Indonesia emphasizes the application of scientific method-based mathematics learning, namely scientific learning. However, the fact is that learning mathematics, especially with plane-shaped materials, often uses conventional methods, monotonous presentation of concepts, and teacher-focused learning approaches. Therefore, learning mathematics should be linked to the realities of everyday life, one of which is through learning that utilizes the cultural context. Culture-based contextual learning is mathematics learning that uses a contextual approach with a cultural context as a starting point to build and connect students' understanding of contextual mathematics to formal mathematics. In this study, the cultural context used is a traditional tool in the form of a random number, which is usually seen by students in everyday life. Tools ancak is a traditional tool commonly used by the people of Sapit village as a place to bring various types of dishes to sacred events. The purpose of this research is to produce a culture-based contextual learning design on the area and perimeter of a square. This research method uses qualitative research with a design research approach to development studies. The results show that tools ancak is one of the traditional tools that can be applied to implement culture-based contextual learning because tools ancak has a physical form that can help students understand mathematics, especially the area and perimeter of a square. In addition, this culture-based contextual learning design is also beneficial for students to learn mathematics, especially the area and perimeter of a square while preserving local culture.